Barriers to efficient provision of healthcare facilities: an experience from a developing country. - Musharraf, Fatima Fakir; Rani, Anooja (Journal of the Pakistan Medical Association, 2021)
Pakistan has nearly 200 million people, of which almost 20 million people live in Karachi, which has 17 tertiary care hospitals, and it is no secret that they are overburdened (1). Despite the healthcare workers’ competency, several issues hinder administering proper care in a tertiary healthcare setup. Firstly, spatial distancing-spatial access to facilities within a hospital also proves a challenge for patients. Patients have little idea regarding specific departments in a large tertiary care hospital due to low literacy rates compounded with a lack of health literacy. At times many patients have reportedly circled the hospital twice and can still not find their desired specialist. A study conducted in Delhi that closely matches Karachi in demographics suggested that patients with one-time visits to secondary care facilities had lower follow-up rates than those who were more familiar with the system (2). Patients may take time to acclimatize to healthcare setup when visiting as first-timers, and if found too challenging to adapt, they may not make an effort again. Unsurprisingly, this renders many facilities- the administration spends, sometimes a fortune, procuring- useless. Continuous...